1986
DOI: 10.1002/1097-0142(19860401)57:7<1337::aid-cncr2820570715>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Lymphadenopathy due to fatal histiocytic proliferative disorder containing michaelis-gutmann bodies

Abstract: A 59-year-old white man had generalized lymphadenopathy, fever, weight loss, and hypercalcemia. Histologic examination of seven lymph nodes from three different anatomic sites revealed a diffuse histiocytic infiltrate containing numerous typical Michaelis-Gutmann (MG) bodies. Histochemical and immunohistochemical results confirmed the histiocytic nature of the predominant cell within the infiltrate. Approximately equal numbers of residual normal B-cells, T-helper, and T-suppressor cells were present. Electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…4-7 Differential diagnoses of nodal infiltrates containing histiocytic cells include infections (mycobacterium-for example, Mycobacterium leprae-toxoplasma, 4 and Whipple's disease 8 ), Rosai-Dorfman disease, lymphangiographic changes, Langerhan's cell histiocytosis, monocytoid B cell hyperplasia, virus associated haemophagocytic syndrome, metastatic melanoma, 8 and malakoplakia. 9 However, the presence of CD68 positive macrophages containing birefringent particles within their cytoplasm confirms the diagnosis of sinus histiocytosis related to previous joint prosthesis surgery. 4 "As the prognosis in cases of Hodgkins lymphoma is often good, the associated lymphadenopathy should not necessarily prevent radical prostatectomy for gland confirmed adenocarcinoma "…”
Section: Discussionmentioning
confidence: 74%
“…4-7 Differential diagnoses of nodal infiltrates containing histiocytic cells include infections (mycobacterium-for example, Mycobacterium leprae-toxoplasma, 4 and Whipple's disease 8 ), Rosai-Dorfman disease, lymphangiographic changes, Langerhan's cell histiocytosis, monocytoid B cell hyperplasia, virus associated haemophagocytic syndrome, metastatic melanoma, 8 and malakoplakia. 9 However, the presence of CD68 positive macrophages containing birefringent particles within their cytoplasm confirms the diagnosis of sinus histiocytosis related to previous joint prosthesis surgery. 4 "As the prognosis in cases of Hodgkins lymphoma is often good, the associated lymphadenopathy should not necessarily prevent radical prostatectomy for gland confirmed adenocarcinoma "…”
Section: Discussionmentioning
confidence: 74%
“…In two other patients with immunodeficiency, secondary pancreatic involvement by adrenal/colonic and retroperitoneal malakoplakia has been described [5,11]. Previously, Dervan et al [6] reported a 59-year-old patient with generalized lymphadenopathy due to a proliferation of macrophages containing typical Michaelis-Gutmann bodies, confirmed by electron microscopy. Our patient reported a history of diabetes mellitus, frequently described in association with malakoplakia and presented with clinical signs and symptoms of chronic pancreatitis, later confirmed by histology.…”
Section: Discussionmentioning
confidence: 99%
“…Zuk et al [ 7 ] described a patient with concurrent malakoplakia and moderately differentiated adenocarcinoma of the pancreas with widespread metastasis of the tumor and subsequent demise of the patient. Reports of malakoplakia involving lymph nodes have been described [ 6 , 8 ] and it appears that diffuse lymph node involvement is usually more commonly seen in immunocompromised patients. The significance of lymph node involvement by malakoplakia is uncertain at present with some reports describing a poor prognostic implication [ 8 ], while in others [ 6 ] the patients have an uneventful postdiagnosis period.…”
Section: Discussionmentioning
confidence: 99%